MFIB 2.0 a major update of the database of protein complexes formed by mutual folding of the constituting protein chains - Fichó Erzsébet; Pancsa Rita; Magyar Csaba; Kálmán Zsófia Etelka; Schád Éva; Németh Zoltán Bálint; Simon István; Dobson László; Tusnády Gábor (NUCLEIC ACIDS RESEARCH, 2025)
While the majority of proteins with available structures are able to fold independently and mediate interactions only after acquiring their folded state, a subset of the known protein complexes contains protein chains that are intrinsically disordered in isolation. The Mutual Folding Induced by Binding (MFIB) database collects and classifies protein complexes, wherein all constituent protein chains would be unstable / disordered in isolation but fold into a well-defined 3D complex structure upon binding. This phenomenon is often termed as cooperative folding and binding or mutual synergistic folding (MSF). Here we present a major update to the database: we collected and annotated hundreds of new protein complexes fulfilling the criteria of MSF, leading to an almost six-fold increase in the size of the database. Many novel features have also been introduced, such as clustering of the complexes based on structural similarity and domain types, assigning different evidence levels to each entry and adding the evidence coverage label that allowed us to include complexes of multi(sub)domain monomers with partial MSF.